Validation of the Model for End‐stage Liver Disease sodium (MELD‐Na) score in the Eurotransplant region. Issue 1 (4th August 2020) - Goudsmit, Ben F. J.; Putter, Hein; Tushuizen, Maarten E.; de Boer, Jan; Vogelaar, Serge; Alwayn, I.P.J.; van Hoek, Bart; Braat, Andries E.
Abstract : The MELD score is used in the Eurotransplant (ET) region to allocate liver grafts. Hyponatremia in cirrhotic patients is an important predictor of death but is not incorporated in MELD. This study investigated the performance of the MELD‐Na score for the ET region. All adult patients with chronic liver disease on the ET liver transplantation waiting list (WL) allocated through lab MELD scores were included. The MELD‐corrected effect of serum sodium (Na) concentration at listing on the 90‐day WL mortality was calculated using Cox regression. The MELD‐Na performance was assessed with c‐indices, calibration per decile and Brier scores. The reclassification from MELD to MELD‐Na score was calculated to estimate the impact of MELD‐Na‐based allocation in the ET region. For the 5223 included patients, the risk of 90‐day WL death was 2.9 times higher for hyponatremic patients. The MELD‐Na had a significantly higher c‐index of 0.847 (SE 0.007) and more accurate 90‐day mortality prediction compared to MELD (Brier score of 0.059 vs 0.061). It was estimated that using MELD‐Na would reduce WL mortality by 4.9%. The MELD‐Na score yielded improved prediction of 90‐day WL mortality in the ET region and using MELD‐Na for liver allocation will very likely reduce WL mortality. Abstract : This study validates the MELD‐Na for the Eurotransplant region, showing that its implementation could reduce waitlist mortality.